Molecular Structural, Hydrogen Bonding Interactions, and Chemical Reactivity Studies of Ezetimibe-L-Proline Cocrystal Using Spectroscopic and Quantum Chemical Approach - Prajapati, Preeti; Pandey, Jaya; Tandon, Poonam; Sinha, Kirti; Shimpi, Manishkumar R. (Frontiers in Chemistry, 2022)
Ezetimibe (EZT) is an anti-cholesterol drug frequently used for the reduction of elevated blood cholesterol levels. With the purpose of improving the physicochemical properties of EZT, in the present work cocrystal of ezetimibe with L-proline has been studied. Theoretical geometry optimization of EZT-L-proline cocrystal, energies, and structure-activity relationship was carried out at DFT level of theory using B3LYP functional complemented by 6-311++G(d,p) basis set. To better understand the role of hydrogen bonding, two different models (EZT+L-proline and EZT+2L-proline) of EZT-L-proline cocrystal were studied. Spectral techniques (FT-IR, FT-Raman) combined with the quantum chemical methodology were successfully implemented for the detailed vibrational assignment of the fundamental modes. It is zwitterionic cocrystal hydrogen-bonded with an OH group of EZT and COO− a group of L-proline. The existence and strength of hydrogen bonds were examined by natural bond orbital analysis (NBO) supported by the quantum theory of atoms in molecule (QTAIM). Chemical reactivity was reflected by HOMO-LUMO analysis. A smaller energy gap in cocrystal in comparison to API shows that cocrystal is softer and chemically more reactive. MEPS and Fukui functions revealed the reactive sites of cocrystals. The calculated binding energy of the cocrystal was −12.82 kcal/mol (EZT+L-proline) and -26.19 kcal/mol (EZT+2L-proline). The comparative study between EZT-L-proline and EZT suggests that cocrystal can be better used as an alternative to comprehend the effect of hydrogen bonding in biomolecules and enhance the pharmacological properties of active pharmaceutical ingredients (API).